Biochemical Characterization of VIM-39, a VIM-1-Like Metallo-β-Lactamase Variant from a Multidrug-Resistant Klebsiella pneumoniae Isolate from Greece - Papagiannitsis, Costas C; Pollini, Simona; De Luca, Filomena; Rossolini, Gian Maria; Docquier, Jean-Denis; Hrabák, Jaroslav (Antimicrobial agents and chemotherapy, 2015)
VIM-39, a VIM-1-like metallo-β-lactamase variant (VIM-1 Thr33Ala His224Leu) was identified in a clinical isolate of Klebsiella pneumoniae belonging to sequence type 147. VIM-39 hydrolyzed ampicillin, cephalothin, and imipenem more efficiently than did VIM-1 and VIM-26 (a VIM-1 variant with the His224Leu substitution) because of higher turnover rates.
Keywords: exprese genu; Řecko; Gene Expression; izoenzymy; sekvence nukleotidů; Klebsiella Infections; Biotransformation; infekce bakteriemi rodu Klebsiella; Imipenem; techniky typizace bakterií; beta-Lactam Resistance; Sequence Analysis, DNA; antibakteriální látky; beta-Lactamases; sekvenční analýza DNA; Microbial Sensitivity Tests; molekulární sekvence - údaje; Klebsiella pneumoniae; beta-laktamasy; ampicilin; hydrolýza; imipenem; kinetika; biotransformace; lidé; Greece; Anti-Bacterial Agents; beta-laktamová rezistence; Humans; mikrobiální testy citlivosti; Isoenzymes; Cephalothin; Bacterial Typing Techniques; Molecular Sequence Data; Base Sequence; Ampicillin; cefalothin; Kinetics; Hydrolysis